The use of aerobic oxidation process and polymer additives in the preparation of activated carbon of oils consumed by chemical treatment - Ammar Hamdoon; Maher Salih Ahmed (College of Education for Pure Sciences, 2011)
Abstract In this study, the activated carbon has been prepared from the spent lubricant oils in the presence of additives which include polymers. Spent lubricant oils and polymers waste products are pollutant materials, it is possible to use these wastes to prepare activated carbon. The process of preparing activated carbon comprises oxidation of spent lubricant oils at different intervals of time. After determining the ideal circumstances for oxidation, the oxidized oil is dealt with additives which are polyethylene, polystyrene, resin of melamine formaldehyde and rubber with additional oxidation at 300 25 °C for 5,6 and 7 hours. The percentage of asphaltene in all above treatments has been determined then, the best samples have been taken according to asphaltene content. Normal and vacuum distillation have been conducted. The vacuum distillation wastes have been taken and treated with KOH (1 unit waste with 2 units KOH) at 55050 °C for three hours. Many tests have been conducted on the prepared activated carbon such as determining the activity of the samples through adsorption of iodine and methylene blue from aqueous media. The density, ash content and humidity were measured and all the properties was compared with the commercial one.